Mental Health Stigma Among Generation Z Students in Salafi Islamic Boarding Schools - Ahmad Guntur; Indari Putri Rahmadanty; Miftakhul Ulfa (Jurnal Ilmiah Kesehatan, 2022)
Salafi Islamic boarding schools adhering to traditional religious learning can potentially create mental health issues. The mental health problems often experienced by Generation Z students in Islamic boarding schools potentially led to the emergence of stigma. This study aims to describe mental health stigma among Generation Z students in Salafi Islamic boarding schools. It used a quantitative design and a survey approach. The population was Generation Z students in Salafi Islamic boarding schools. Furthermore, there were 155 samples by stratified random sampling. This study was carried out in 3 boarding schools in Bantur District, Malang Regency, from January to February 2022. The variable was mental health stigma. The data were collected by distributing a questionnaire to Generation Z students at Salafi Islamic boarding schools in the Bantur District. The questionnaire used the Peer Mental Health Stigmatization Scale (PMHSS). The PMHSS consisted of 2 indicators: Stigma agreement (self-stigma) and stigma awareness (social stigma). Data analysis used median and percentile values because the data was not normally distributed. Normality test used Kolmogorov-Smirnov using SPSS Statistics 25. The results showed that social stigma had a median value of 40, self-stigma had 40, and overall mental health stigma had 80. In conclusion, Generation Z students in the Salafi Islamic boarding schools had a high mental health stigma. Therefore, efforts to reduce and prevent the Stigma in Salafi Islamic boarding schools through a technology-centered approach and cross-sectorial collaboration with Public Health Center or health workers are crucial.